The mental health of asbestos-exposed subjects with pleural abnormalities - Franklin, P.; Robinson, M.; Abaogye-Sarfo, P.; Samuel, L.; Olsen, N.; Mina, R.; Musk, A.; Reid, Alison (2014)
Purpose: To examine the effect of knowledge of radiographic abnormalities on the mental health of asbestos-exposed people with and without pleural abnormalities. Methods: Subjects were former asbestos mine and mill workers and residents of the mining town who had participated in an annual health review program. Pleural abnormalities (pleural plaques, diffuse pleural thickening and asbestosis) were determined from plain chest X-rays. All Participants completed a questionnaire on mental health status (SF-12) and locus of control (LOC). Results: There were no significant differences between asbestos-exposed people with and without radiographic abnormalities for either the SF-12 mental health score or LOC. However, the asbestos-exposed cohorts had lower mental health scores compared with a random sample of the local population. Conclusion: The presence of pleural abnormalities did not further affect the mental health of asbestos-exposed people beyond a decrement associated with exposure per se.